Good Corporate Governance, Profitability, Interest Rate Against Company Financial Distress With Company Size As Moderating Variable - Great Hangarabhima (Universitas Syiah Kuala, 2023)
The banking business sector has a vital role and function in economic development in Indonesia. Theoretically, the bank has a role as an agent of trust, which means that a bank as a financial institution carries out every operational activity based on trust in raising and channelling funds. Furthermore, it can be understood that the sustainability of the banking industry is very dependent on public trust; if public trust decreases, it will result in a bank experiencing a crisis. This study analyzes data quantitatively, with the design of this study namely testing the existing hypotheses to find out the effect of Financial Distress as the dependent variable. The t-test results prove that the variable Institutional Ownership (IC) has no significant effect on financial distress. Company data published on the Indonesia Stock Exchange concludes that the variables KI, KM, ROA, KI*Size, and KM*SIZE positively affect financial distress. Management is expected to be able to continue to innovate and develop technology correctly and in a planned manner, besides that management must also be able to manage the company's financial performance properly so that it can make the right decisions in carrying out the company's operational activities so that financial distress does not occur.